Association between Periodontal Disease and the Intake of Carbohydrate, Fat and Total Calories in Humans. - Alhassani, Ahmed. (2017)
Abstract: Background: There is increasing evidence in the literature about the association between diet and periodontal disease. Due to the proposed effect of diet on oral and systemic environments, we hypothesized that there is an association between periodontal disease and carbohydrate, fat and total caloric intake. Methods: Data from the National Health and Nutrition Examination Survey (NHANES) 2009-2010 was used. After the application of inclusion and exclusion criteria, 2636 individuals were included in the sample. The outcome variable was periodontitis, defined as the presence of at least one site with both attachment loss ≥3mm and probing depth ≥4mm. Exposure variables were: percentage of calories in diet from carbohydrate, percentage of calories in diet from fat, and total caloric intake. The 2010 Dietary Guidelines for Americans were used to categorize carbohydrate and fat into 3 categories each. Caloric requirement for each subject was estimated using Harris-Benedict equation and individual's reported level of physical activity. Actual caloric intake was compared with the estimated caloric requirement in order to classify participants into: reduced, average and excess caloric intake. The following covariates were selected as potential confounders: smoking, diabetes, age, sex, race/ethnicity, education, socioeconomic level, waist circumference and whether a subject has had previous periodontal treatment or not. Descriptive statistics, bivariate analysis and logistic regression models were used for data analyses. Results: The prevalence of periodontitis in the sample was 39.1%. A statistical significance was detected between the outcome variable and all the covariates. No statistical significance was found between any of the exposure variables and periodontitis. Conclusions: the results of this study showed no statistically significant association between periodontal disease and carbohydrate, fat and total caloric intake. More studies are needed to further investigate such association.; Thesis (M.S.)--Tufts University, 2013.; Submitted to the Dept. of Periodontology.; Advisor: Rory O'Neill.; Committee: Wanda Wright, Paul Stark, Carole Palmer, and Elizabeth Krall Kaye.; Keywords: Dentistry, Epistemology, and Nutrition.